Comparative Analysis of Traffic Light Control Mechanism for Emergency Vehicle - Dave, Jashvantkumar Rajnikant; Panchal, Shailesh (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Traffic congestion during peak hours is a critical issue worldwide. Increasing number of vehicles, hence, traffic jams primarily near cross roads results into significant delay in emergency services vehicles. Surveys suggest that lives of many patients can be saved if emergency medical services could be reached in time. With the advancements in sensor and communication technology, it is now possible to provide improved solution to the delay resulting due to heavy traffic. Suggested solutions range from giving signalling priority to emergency vehicles to establishing a dedicated network to track the position of the emergency vehicle and ensuring an open route to the destination. This paper, explores various mechanisms proposed for effective evacuation of vehicles on the route of emergency vehicle. Paper attempts to provide broader view and state of the work done in the said area. The study perceives the boundaries of existing traffic light pre-emption mechanisms, leading to several significant gaps that require further exploration. These gaps include implementation of proper system architecture, use of efficient communication technology, inclusion of real-time traffic data for optimized pre-emption of traffic light, prioritizing emergency vehicles to resolve conflict between multiple emergency vehicles and misuse prevention.